Influence of dopamine receptor gene polymorphisms on circulating T lymphocytes: A pilot study in healthy subjects - Cosentino, Marco; Ferrari, Marco; Kustrimovic, Natasa; Rasini, Emanuela; Marino, Franca (Human immunology, 2015)
Dopamine is a key transmitter in the neuroimmune network, acting through five dopaminergic receptors (DR): the D1-like D1 and D5 and the D2-like D2, D3 and D4. Several DR gene variants exist and may affect DR expression and activity. We assessed total lymphocytes, CD3+, CD4+ and CD8+ T lymphocytes in peripheral blood of healthy subjects and their association with selected DR gene variants (DRD1 rs4532 and rs686, DRD5 rs6283, DRD2 rs1800497 and rs6277, DRD3 rs6280 and rs1800828, DRD4 rs747302 and 7 48-base pair VNTR). DRD1 rs4532 and rs686 and DRD5 rs6283 were associated with total lymphocytes, and with CD3+ and CD4+ (but not CD8+) T lymphocytes, while none of the D2-like DR gene variants showed any association with lymphocyte counts. An arbitrary score based on the activity of D1-like vs D2-like DR correlated with total lymphocytes, CD3+ and CD4+ T cells (but not with CD8+ T cells). The association between D1-like DR gene variants and lymphocyte count, and in particular with CD4+ (but not CD8+) T lymphocytes, may imply a functional prevalence of D1-like over D2-like DR in CD4+ T cells. This is the first study showing an influence of DR gene polymorphisms on lymphocyte count, and in particular on CD4+ T cells. Future studies should address the possible association between DR gene variants and the immune function in health and disease. The relevance of these findings for the immune effects of dopaminergic agents should be also carefully examined.